2003
DOI: 10.3168/jds.s0022-0302(03)73769-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Affecting Milk Production Traits in Finnish Ayrshire Dairy Cattle

Abstract: A whole genome scan of Finnish Ayrshire was conducted to map quantitative trait loci (QTL) affecting milk production. The analysis included 12 half-sib families containing a total of 494 bulls in a granddaughter design. The families were genotyped with 150 markers to construct a 2764 cM (Haldane) male linkage map. In this study interval mapping with multiple-marker regression approach was extended to analyse multiple chromosomes simultaneously. The method uses identified QTL on other chromosomes as cofactors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
111
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 33 publications
19
111
0
Order By: Relevance
“…IV). On these chromosomes, fertility QTL were detected in the single trait regression analysis close to milk QTL [46] detected earlier and some of them had QTL regions affecting two different fertility traits. The analysed traits were DO, FT, CM, NRR, MY, PY, and FY.…”
Section: Multi-trait Analysismentioning
confidence: 56%
See 4 more Smart Citations
“…IV). On these chromosomes, fertility QTL were detected in the single trait regression analysis close to milk QTL [46] detected earlier and some of them had QTL regions affecting two different fertility traits. The analysed traits were DO, FT, CM, NRR, MY, PY, and FY.…”
Section: Multi-trait Analysismentioning
confidence: 56%
“…When comparing the fertility QTL with the positions of the milk trait QTL detected in an earlier study in the same families [46], several milk and fertility QTL were found on the same chromosomes. For example, on BTA25, where QTL were detected for DO and FT at the end of the chromosome, QTL for milk yield and protein yield were also detected.…”
mentioning
confidence: 76%
See 3 more Smart Citations